The PENGARUH MODEL REQOL (REAL QUEST OUTDOOR LEARNING) TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR FISIKA SISWA SMA - fadilla pusvitasari Azis; I Wayan Distrik; Viyanti Viyanti (Program Studi Pendidikan Fisika FKIP Universitas Muslim Maros, 2023)
The goal of this study is to evaluate the impact of the ReQOL model on high school students' critical thinking and cognitive learning outcomes. This experimental research method uses pre-test and post-test questions to collect quantitative data from the results of students' critical thinking assessments. All of the pupils in the XIPA class at SMA Negeri 1 Natar made up the study's population. Purposive sampling is used to choose the research sample. Class X IPA III served as the control class in this study, and class X IPA VIII served as the experimental class. Test questions and observation logs were used to obtain the data. Utilizing independent sample T tests and effect size. According to the findings, there was a difference between students who used the ReQOL learning model and those who used Direct Instruction when learning about harmonic vibrations. This difference was based on the significance values of the test Smirnov, which were 0.076 for the pre-test and 0.167 for the post-test in the experimental class. The level of significance of the data is revealed to be 0.000 < 0.05 based on test results from an independent sample T test, indicating that the ReQOL model has a significant impact on improving high school students' critical thinking abilities and academic performance. Based on these results it can be concluded that there is an influence of critical thinking skills and student learning outcomes following the ReQOL learning model in class X IPA physics at SMA Negeri 1 Natar.